Radiography of a normal fault system by 64, 000 high‐precision earthquake locations: The 2009 L'Aquila (central Italy) case study. Issue 3 (31st March 2013) - Valoroso, L.; Chiaraluce, L.; Piccinini, D.; Di Stefano, R.; Schaff, D.; Waldhauser, F.
Abstract: [1] We studied the anatomy of the fault system where the 2009 L'Aquila earthquake (MW 6.1) nucleated by means of 64 k high‐precision earthquake locations spanning 1 year. Data were analyzed by combining an automatic picking procedure for P and S waves, together with cross‐correlation and double‐difference location methods reaching a completeness magnitude for the catalogue equal to 0.7 including 425 clusters of similar earthquakes. The fault system is composed by two major faults: the high‐angle L'Aquila fault and the listric Campotosto fault, both located in the first 10 km of the upper crust. We detect an extraordinary degree of detail in the anatomy of the single fault segments resembling the degree of complexity observed by field geologists on fault outcrops. We observe multiple antithetic and synthetic fault segments tens of meters long in both the hanging wall and footwall along with bends and cross fault intersections along the main fault and fault splays. The width of the L'Aquila fault zone varies along strike from 0.3 km where the fault exhibits the simplest geometry and experienced peaks in the slip distribution, up to 1.5 km at the fault tips with an increase in the geometrical complexity. These characteristics, similar to damage zone properties of natural faults, underline the key role of aftershocks in fault growth and co‐seismic rupture propagation processes. Additionally, we interpret the persistent nucleation of similar events at the seismicity cutoff depth as the presence of a rheological (i.e., creeping) discontinuity explaining how normal faults detach at depth. Key Points: The fault architecture resembles features observed at outcrop scale Normal faults terminate at depth along a basal creeping decòllment Aftershocks image the damage zone width which is comparable to geological ones